Impact of early fructose intake on metabolic profile and aerobic capacity of rats - Botezelli José D; Ribeiro Carla; Cambri Lucieli T; Ghezzi Ana C; Mello Maria AR (Lipids in Health and Disease, 2011)
Abstract Background Metabolic syndrome is a disease that today affects millions of people around the world. Therefore, it is of great interest to implement more effective procedures for preventing and treating this disease. In search of a suitable experimental model to study the role of exercise in prevention and treatment of metabolic syndrome, this study examined the metabolic profile and the aerobic capacity of rats kept early in life on a fructose-rich diet, a substrate that has been associated with metabolic syndrome. Methods We used adult female Wistar rats fed during pregnancy and lactation with two diets: balanced or fructose-rich 60%. During breastfeeding, the pups were distributed in small (4/mother) or adequate (8/mother) litters. At 90 days of age, they were analyzed with respect to: glucose tolerance, peripheral insulin sensitivity, aerobic capacity and serum glucose, insulin, triglycerides, total cholesterol, LDL cholesterol and HDL cholesterol concentrations as well as measures of glycogen synthesis and glucose oxidation by the soleus muscle. Results It was found that the fructose rich diet led the animals to insulin resistance. The fructose fed rats kept in small litters also showed dyslipidemia, with increased serum concentrations of total cholesterol and triglycerides. Conclusion Neither the aerobic capacity nor the glucose oxidation rates by the skeletal muscle were altered by fructose-rich diet, indicating that the animal model evaluated is potentially interesting for the study of the role of exercise in metabolic syndrome.